2018
DOI: 10.1007/s00436-018-5895-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of miconazole/clotrimazole and praziquantel combinations against the liver fluke Opisthorchis felineus in vivo and in vitro

Abstract: The liver fluke Opisthorchis felineus (Rivolta, 1884) is the causative agent of opisthorchiasis felinea in Eurasia. Opisthorchiasis is a serious human and fish-eating animal's disease affecting bile ducts and the gall bladder. Currently, the main drug for specific therapy of opisthorchiasis is praziquantel. We have previously shown that azole inhibitors of O. felineus cytochrome P450 significantly reduced survival of the worms in vitro. Here, we studied in vitro anthelmintic effects of drug combinations involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Similar findings were seen to those for TBD [147]. The synergistic effect of the PZQ-CTZ and PZQ-MCZ combinations observed in vitro, unfortunately were not evident in vivo [155]. For enhanced efficacy, different dosing ration or schedule may be necessary.…”
Section: Opisthorchiasissupporting
confidence: 72%
“…Similar findings were seen to those for TBD [147]. The synergistic effect of the PZQ-CTZ and PZQ-MCZ combinations observed in vitro, unfortunately were not evident in vivo [155]. For enhanced efficacy, different dosing ration or schedule may be necessary.…”
Section: Opisthorchiasissupporting
confidence: 72%
“…Another important motivation for using antioxidants as an adjunctive agent in a combination therapy is that in chronic opisthorchiasis, the accumulation of oxidative damage increases with the duration of infection and correlates with the disease severity [3,4]. Moreover, resolution of the pathological hepatobiliary changes is not seen in all cases after the flukes have been eliminated [5,10]. Unfortunately, these individuals may be at high risk of severe hepatobiliary sequelae including cholangiocarcinoma [5].…”
Section: Discussionmentioning
confidence: 99%
“…The current gold standard for measuring drug effectiveness for most helminth parasites is in vitro testing performed by microscopy, which included parasite counting and evaluation of motility and morphology [6,9,10,15]. Although reduced motility is not an ideal metric of mortality, it is a reasonable reduced viability analogue when screened for anthelmintic activity [6,9,10,15]. These assays of adult helminths revealed that antioxidants from both the natural set and synthetic set proved to be effective compounds (Table 1, Figure 2A).…”
Section: Motility Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Worms remaining in the hepatobiliary system on day 14 post-treatment were counted after killing the hamsters by CO 2 asphyxiation. Drug activity was expressed as a worm burden reduction (WBR) as described elsewhere [8, 16]. Briefly, WBRs were calculated as follows: (a − b)/a × 100, where a is the average worm count in the control group upon dissection, and b is the average worm count in the treated group upon dissection.…”
Section: Methodsmentioning
confidence: 99%